Genistein Exposure Interferes with Pharmacokinetics of Celecoxib in SD Male Rats by UPLC-MS/MS - Xiang Zheng; Jian Wen; Teng-hui Liu; Qiu-Geng Ou-yang; Jian-ping Cai; Hong-yu Zhou (Biochemistry Research International)
Objective. To discuss the effects of genistein on the metabolism of celecoxib in vitro and in vivo. Method. In vitro, the effects of genistein on the metabolism of celecoxib were studied using rat and human liver microsomes. In vivo, pharmacokinetics of celecoxib was evaluated in rats with or without genistein. Fifteen Sprague-Dawley (SD) rats were randomized into three groups: celecoxib (A group), celecoxib and 50 mg/kg genistein (B group), and celecoxib and 100 mg/kg genistein (C group). Single dose of 33.3 mg/kg celecoxib was orally administered 30 min after genistein ig. At 0.5, 1, 2, 3, 4, 6, 8, 10, 12, and 24 h after celecoxib administration, 300–400 µl blood samples were collected and the concentration of celecoxib was analyzed by ultrahigh-performance liquid chromatography-tandem mass spectrometry system. Result. Genistein showed notable inhibitory effects on three microsomes. It affected pharmacokinetics of celecoxib in vivo experiments. Genistein had dramatically ability to suppress CYP2C9∗1 and ∗3. After pretreatment with genistein, AUC and Cmax of the C group were higher than B group. CLz/F of C group was lower than the B group. Conclusion. Genistein inhibits the conversion of celecoxib in vitro and in vivo. So, the dosage of celecoxib should be adjusted if it was used associated with genistein.